2011
DOI: 10.1016/j.neuro.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury-induced alterations in astrocyte functions are attenuated by ebselen

Abstract: Methylmercury (MeHg) preferentially accumulates in glia of the central nervous system (CNS), but its toxic mechanisms have yet to be fully recognized. In the present study, we tested the hypothesis that MeHg induces neurotoxicity via oxidative stress mechanisms, and that these effects are attenuated by the antioxidant, ebselen. Rat neonatal primary cortical astrocytes were pretreated with or without 10 μM ebselen for 2 hours followed by MeHg (0, 1, 5, and 10 μM) treatments. MeHg-induced changes in astrocytic [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 98 publications
(98 reference statements)
1
49
0
Order By: Relevance
“…Moreover, oxidative stress also plays an important role in degenerative conditions such as metalinduced toxicity. It is well known that ROS mediate MeHg-induced neurotoxicity in several experimental models, and mitochondrial changes may initiate a cascade of events culminating in cell death (apoptosis or necrosis) Bernardi et al, 1998;Kroemer and Reed, 2000;Yin et al, 2011). At present, several investigators reported that apoptosis occurs as result of organic Hg-mediated toxicity (dos Santos et al, 2016;Sokolowski et al, 2011;Ceccatelli et al, 2010), but the molecular mechanisms are not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oxidative stress also plays an important role in degenerative conditions such as metalinduced toxicity. It is well known that ROS mediate MeHg-induced neurotoxicity in several experimental models, and mitochondrial changes may initiate a cascade of events culminating in cell death (apoptosis or necrosis) Bernardi et al, 1998;Kroemer and Reed, 2000;Yin et al, 2011). At present, several investigators reported that apoptosis occurs as result of organic Hg-mediated toxicity (dos Santos et al, 2016;Sokolowski et al, 2011;Ceccatelli et al, 2010), but the molecular mechanisms are not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…After that, other experiments confirmed this finding in tuna fish [60] and other animals. Thus, in general, the simultaneous administration of selenite counteracts the negative impacts of exposure to inorganic mercury, particularly in relation to neurotoxicity, fetotoxicity [61][62][63][64][65] and cardiovascular diseases [66]. However, some authors have suggested that further studies of the potential interplay of these elements in cardiovascular diseases are warranted, especially in relation to fish consumption [67].…”
Section: Protection Against Mercury Toxicity By Seleniummentioning
confidence: 99%
“…This further confirmed our observation that energy deficit occurred in MN9D cells treated with the two toxicants. MeHg has been shown to inhibit OXPHOS and increase cellular reactive oxygen species (ROS) (Mazzio and Soliman, 2012), and treatment with glutathione peroxidase mimetic (ebselen) reverses MeHg-induced neurotoxicity (Yin et al, 2011). In addition to the disruption of the OXPHOS pathway, we also showed that MeHg changed 5 proteins (GSR, G6PDX, IDH1, GCLM and HNRPLL) involved in glutathione metabolism.…”
Section: Discussionmentioning
confidence: 73%